The Influence of Green Living, Green Product, and Price on Purchasing Stainless Straw in the Millennial Generation of Pekalongan City - Zulafa, Nadlia Nikhla; Yunitarini, Siti; Milasari, Dian (ProBisnis : Jurnal Manajemen, 2023)
This study aims to examine and analyze the effects of Green Living, Green Products, and Price on Stainless Straw Purchase Decisions on the Millennial Generation of Pekalongan City. This type of research is casual research with a quantitative approach. The analysis technique used is multiple linear regression analysis, t test and determination analysis. The population in this study is unknown, so the sampling technique used was non-probability sampling with purposive sampling. The sample used in this study is the people of Pekalongan City, belonging to the millennial generation, who have already purchased and used stainless straw. The determination of respondents was done using the Rao Purba formula so that 97 respondents were obtained. The results of this study indicate that: (1) green living has a positive and significant effect on purchasing decisions for stainless straw in the millennial generation of Pekalongan City; (2) green products have a positive and significant effect on purchasing decisions for stainless straw in the millennial generation of Pekalongan City; (3) price has a positive and insignificant effect on purchasing decisions for stainless straw in the millennial generation of Pekalongan City; and (4) green living, green products, and price have an influence on purchasing decisions by 55.9%, while the remaining 44.1% is influenced by other variables not examined in this study.